2000
DOI: 10.1103/physrevlett.84.1471
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulation of Aging and Rejuvenation in Glasses

Abstract: Slow structural relaxation ("aging") observed in many atomic, molecular, and polymeric glasses substantially alters their stress-strain relations and can produce a distinctive yield point. Using Monte Carlo simulation for a binary Lennard-Jones mixture, we have observed these phenomena and their cooling-rate dependences for the first time in an atomistic model system. We also observe that aging effects can be reversed by plastic deformation ("rejuvenation"), whereby the system is expelled from the vicinity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
172
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(188 citation statements)
references
References 20 publications
(35 reference statements)
16
172
0
Order By: Relevance
“…As the cooling rate decreases, the yield stress and strain increase because fewer and smaller particle rearrangements occur. However, at large strains, beyond the yield strain, σ(γ), as well as U (γ), become independent of cooling rate [2,32]. Previous studies have shown that the number of energy minima grows exponentially with the average potential energy [28,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cooling rate decreases, the yield stress and strain increase because fewer and smaller particle rearrangements occur. However, at large strains, beyond the yield strain, σ(γ), as well as U (γ), become independent of cooling rate [2,32]. Previous studies have shown that the number of energy minima grows exponentially with the average potential energy [28,39].…”
Section: Resultsmentioning
confidence: 99%
“…The cooling rate determines the fictive temperature, which defines the average energy of the glass in the potential energy landscape [27,28]. The fictive temperature significantly affects mechanical properties, such as ductility [14,29,30], shear band formation [31], and stress versus strain [2,32]. Prior work has characterized the disappearance of minima in the energy landscape and resulting particle rearrangements versus applied strain [26,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…First, the free volume has been notoriously difficult to define experimentally. Also, this model does not seem compatible with the observed aging in glassy solids under constant volume conditions [13], and cannot predict the aging behavior under complex thermo-mechanical histories. Modern energy landscape theories describe the aging process as a series of hops between progressively deeper traps in configuration space [14,15].…”
Section: Introductionmentioning
confidence: 85%
“…For instance, calculations of particle correlation functions have shown explicitly that the characteristic time scale for particle relaxations increases with wait time [19]. Recent work [13,20] has focused on the effect of aging on the mechanical properties; results showed that the shear yield stress (defined as the overshoot or maximum of the stress-strain curve) in deformation at constant strain rate generally increases logarithmically with t w . Based on a large number of simulations at different strain rates and temperatures, a phenomenological rate-state model was developed that describes the combined effect of rate and age on the shear yield stress for many temperatures below the glass transition [21].…”
Section: Introductionmentioning
confidence: 99%
“…This transformation is irreversible since once the stress is removed, the system remains in its "aged" state. On the contrary, large stresses move the system far from its initial state, which eventually leads to rejuvenation [27,28]. Although previous accelerated aging techniques have sometimes been shown to yield results that do not match spontaneous aging [26], we ensured that the present protocol predicts a realistic relaxation by checking that, upon relaxation, a hyperquenched glass evolves toward the inherent configurations of the more slowly cooled supercooled liquids [1].…”
mentioning
confidence: 98%